2020
DOI: 10.1186/s12888-020-02542-y
|View full text |Cite
|
Sign up to set email alerts
|

Empirical examination of executive functioning, ADHD associated behaviors, and functional impairments in adults with persistent ADHD, remittent ADHD, and without ADHD

Abstract: Background: Previous studies suggest that childhood attention deficit hyperactivity disorder (ADHD) may continue in adulthood, producing adverse effects. Therefore, identifying factors that help to differentiate characteristics of ADHD persistence and remission has practical implications for evaluation and treatment. The first aim of this study was to analyze differences in executive functions (shift, working memory, inhibition, and plan/organize), symptoms associated with ADHD (inattention, hyperactivity, emo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…Precisely, ADHD is an umbrella term for a set of trait-like features and a developmental trajectory alike (Asherson et al 2016 ; Franke et al 2018 ; Fredriksen et al 2013 ). For this reason, the day-to-day adverse consequences of ADHD are not limited to various social, academic, and occupational circumstances of the individual’s life (Roselló et al 2020 ). In fact, as neatly coined by Faraone et al ( 2015 ), ‘the disorder directly affects perceptions of well-being’ — the statement which, from the standpoint of everyday clinical practice, translates into a mind-boggling spectrum of patient-important outcomes (Bölte et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Precisely, ADHD is an umbrella term for a set of trait-like features and a developmental trajectory alike (Asherson et al 2016 ; Franke et al 2018 ; Fredriksen et al 2013 ). For this reason, the day-to-day adverse consequences of ADHD are not limited to various social, academic, and occupational circumstances of the individual’s life (Roselló et al 2020 ). In fact, as neatly coined by Faraone et al ( 2015 ), ‘the disorder directly affects perceptions of well-being’ — the statement which, from the standpoint of everyday clinical practice, translates into a mind-boggling spectrum of patient-important outcomes (Bölte et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, connections of ADHD to religious behaviors may not be completely explained by the direct effects of symptoms like short attention span or impulsivity. Several studies have shown that adults with remitted ADHD show functional impairment, although less prominent than those with active and severe symptoms (Hechtman et al, 2016; Klein et al, 2012; Roselló et al, 2020). If not all of observed psychosocial function is due to direct effects of symptoms, it may be partially attributable to attitudes and lifestyles that have evolved over the course of childhood and adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is not surprising that not only the severity of ADHD, but also learning difficulties in the past have been related to persistence of ADHD into adulthood in previous literature (Mano et al ., 2019; Rabiner, Anastopoulos, Costello, Hoyle, McCabe & Swartzwelder, 2009). More specifically, recent studies (Roselló, Berenguer, Baixauli, et al ., 2020a; Roselló, Berenguer, Martínez‐Raga, Baixauli & Miranda, 2020b) showed that people whose ADHD symptoms persisted into adulthood, manifested a low performance in executive functions (such as inhibition, shift, working memory, and plan/organize) and presented functional impairments in family, social, academic, and risky activities.…”
Section: Discussionmentioning
confidence: 99%